Characterization of cellular responses of UV-irradiated keratinocytes to Lignosus Rhinocerus (TM02) extracts - Lim, Hui Sin (2022)
Prolong exposure to ultraviolet radiation (UV) induces pathophysiological changes to epithelial cells such as keratinocytes and melanocytes, including oxidative damages to DNA and lipids as well as other cellular components, leading to cellular transformation and generation of cancerous cells. In addition, prolong UV exposure can lead to photo-aging and skin hyperpigmentation. Thus, mitigating the negative impacts of UV can protect skin from the insults induced by UV. Natural products have been shown to possess active ingredients that are beneficial to human skin and are preferred by consumers of skin care products when compared to the synthetic or chemical ingredients. To identify plant extracts that confer UV protective benefits to epithelial cells, Lignosus rhinocerus extracts were prepared from TM02 tiger milk mushroom sclerotia powder and screened with bio-assays to identify UVB protective activities in human keratinocytes, HaCaT. The TM02 methanol extract prepared with the concentration of 15.625, 31.25, 62.5 and 125 μg/ml was pre-incubated with HaCaT cells before UVB irradiation and its impacts on HaCaT cells were examined using bio-assays, including cell viability, DNA damage, apoptosis, cytochrome c release assays as well as gene and protein expression analyses. Methanol extract of TM02 increased cell viability and reduced DNA damages of UVB-irradiated HaCaT cells in a dose-dependent manner. In addition, pre-treatment of HaCaT cells with TM02 extract led to 39% reduction of cyclobutane pyrimidine dimers with increases in DNA repair activities in UVB-irradiated HaCaT cells in comparison to UVB-irradiated group without TM02 treatment. The enhanced DNA damage repair activity was identified by gene expression analysis using RT-PCR and the results showed the up-regulation of translesion synthesis (TLS) DNA polymerases, including POLH, REV1 and POLQ in the HaCaT cells pre-treated with TM02 followed by UVB irradiation. Importantly, pre-treatment of HaCaT cells with TM02 increased the expression of Bcl-xL and Bcl-2 proteins and reduced the release of mitochondrial cytochrome c of UVB-irradiated HaCaT cells, suggesting that TM02 confers UV protection to HaCaT cells through up-regulation of Bcl-2 and Bcl-xL. To substantiate the role of Bcl-xL in UVB-irradiated HaCaT cells, stable clones of Bcl-xL, which overexpressed Bcl-xL proteins were generated in HaCaT cells and were shown to confer resistance to UVB, resulting in the increase in cell viability when compared to vector control stable clone. Together, these results showed that TM02 confers UVB protective benefits to HaCaT cells through up-regulations of Bcl-2 and Bcl-xL as well as DNA repair proteins. The results thus provide novel insights into the mechanisms of action of TM02 in keratinocytes which may lead to the incorporation of TM02 as UV protective ingredient in the skin care products.